Analysis of Types of Moral Value Reflected by The Characters in Toy Story Movie - Firdayanti , I Gusti Ayu Risna; Sulatra, I Komang; Ariyaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2023)
This research aimed to analyze the types of moral value found in Toy Story movie and the way the characters in the movie reflected the values. This research used Toy Story movie as the data source. This research used qualitative method and the data were analyzed descriptively. The data found in the study were classified by the types of moral value, based on the theory from Audi (2007). The purpose of this study was to find out the moral values reflected by every character in the toy story movie. Based on the analysis, it was found that the moral values deal with t social values in terms of behaviour, relation, interaction and also the social groups that reflected by the characters. In this research the moral values of the characters were reflected by the performance of the characters in the movie. The reflection of such value can be seen from their action and incidents including conversation among the characters in Toy Story movie. The result of the study showed the relation between the actions from the character of Toy Story movie and the conversation affect the character’s attitude that showed how the moral is created in the movie.